The relationship between university students’ goal orientation and academic achievement. The mediating role of motivational components and the moderating role of achievement emotions - Frumos, Florin-Vasile; Leonte, Roxana; Candel, Octav Sorin; Ciochină-Carasevici, Laura; Ghiaţău, Roxana; Onu, Camelia (Frontiers in Psychology, 2024)
The present study aims to expand the understanding of the role played by achievement emotions in the learning process and academic achievement of university students. We investigated how achievement emotions moderate the direct and indirect associations between mastery and performance goal orientation and academic achievement. Also, we used as mediators the motivational components from theoretical framework proposed by Pintrich and de Groot (1990). 274 Romanian university students (Mage=20.23, 84.7% women) participated in the study. Moderated mediation analyses indicated that self-efficacy was the only significant mediator, and this relationship was moderated by hope, pride and hopelessness. In addition, the links between mastery and performance approach goals and motivational components are stronger when the positive emotions are higher and the negative ones are lower. Mastery avoidance goals were linked with high scores of motivational components at higher levels of negative and lower levels of positive achievement emotions, whereas the association of avoidance goals with motivational components was moderated by two positive emotions (pride and enjoyment). The patterns derived from the moderating role of achievement emotions in the relationships between goal orientation, motivational components and academic achievement, alongside several inconsistent results and implications in theory and education, are discussed.